2014
DOI: 10.1016/j.ijchv.2014.03.004
|View full text |Cite
|
Sign up to set email alerts
|

Study of vitamin D deficiency prevalence in acute myocardial infarction

Abstract: BackgroundDeficiency of 25-hydroxy vitamin D [25(OH)D] is a treatable condition that has been associated with coronary artery disease and many of its risk factors. A practical time to assess for 25(OH)D deficiency, and to initiate treatment, is at the time of an acute myocardial infarction(AMI). The prevalence of 25(OH)D deficiency and the characteristics associated with it in patients with acute myocardial infarction are unknown.MethodsIn this study 25(OH)D was assessed in 314 subjects enrolled in a Sri Jayad… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
16
1
1

Year Published

2015
2015
2020
2020

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 28 publications
(25 citation statements)
references
References 29 publications
3
16
1
1
Order By: Relevance
“…Vitamin D is also now considered a prognostic factor for acute myocardial infarction and CAD [32,35-37]. In addition, Jablonski et al [38] found endothelial dysfunction in adults with low 25(OH)D 3 , as opposed to patients with normal levels, through the measurement of nuclear factor-κB (0.59 ± 0.07 vs. 0.44 ± 0.05, p < 0.05) and other pro-inflammatory cytokines in endothelial cells.…”
Section: Methodsmentioning
confidence: 99%
“…Vitamin D is also now considered a prognostic factor for acute myocardial infarction and CAD [32,35-37]. In addition, Jablonski et al [38] found endothelial dysfunction in adults with low 25(OH)D 3 , as opposed to patients with normal levels, through the measurement of nuclear factor-κB (0.59 ± 0.07 vs. 0.44 ± 0.05, p < 0.05) and other pro-inflammatory cytokines in endothelial cells.…”
Section: Methodsmentioning
confidence: 99%
“…In this study P<0.05 was found demonstrating significant association of Vitamin D levels and AMI. 18 Taking Vitamin D level ≤20 ng/ml as deficient, Odds ratio of vitamin D was calculated in cases compared to controls and adjusted with other risk factors as co varieties. The adjusted odd ratio (AOR) was 3.034 & its 95% Confidence Interval (CI) was 1.119-8.225.…”
Section: Discussionmentioning
confidence: 99%
“…Normal 25(OH) D levels are 30 ng/ml, and patients with levels <30 and >20 ng/ml were classified as in sufficient and those levels with 20 ng/ml as deficient. 1…”
Section: Sample Sizementioning
confidence: 99%
“…There is need for further investigations to know the other non-traditional risk factors. 1 The common non-traditional risk factors are persons living in high altitudes, decreased sun exposure, dark skinned people.…”
mentioning
confidence: 99%